Study of prescribing errors of two different prescription systems: pre-printed prescription from historical medication and hand-written prescription - Nisa Sae-lim; Ploylarp Lertvipapath (Faculty of Pharmacy, Mahidol University, 2022)
A retrospective observational study of 1,160 prescriptions with prescribing errors from a large academic hospital in Thailand from 2014 to 2017. The aims of this study are to explore the proportion of prescribing error from pre-printed prescriptions and measure the frequency of prescribing errors in pre-printed versus hand-written prescriptions. Prescriptions with prescribing errors were stratified sampling and bootstrap resampling, then classified into 1) pre-printed historical medication prescriptions or pre-printed prescriptions 2) hand-written prescriptions. Some missed prescribing errors of each type of prescription were more identified by comparing the prescriptions with the medical records. Pre-printed prescriptions with prescribing errors constituted 767 (66%) of all collected prescriptions. The most commonly encountered prescribing error was "incomplete medication list in medical record", while 393 (34%) hand-written prescriptions were found to have the wrong dosage strength. Hand-written prescriptions were 1.45 times more likely to have a major error compared to pre-printed prescriptions (OR: 1.45, 95%CI: 1.08-1.94, P 0.012). Although using pre-printed prescription can reduce some prescribing errors such as wrong dosage strength that occur with hand-written prescriptions, pre-printed prescriptions were found to have other prescribing errors. Procedures to improve the prescribing system to increase patient safety are needed.